2016
DOI: 10.1037/spq0000135
|View full text |Cite
|
Sign up to set email alerts
|

Association of acculturative stress, Islamic practices, and internalizing symptoms among Arab American adolescents.

Abstract: Although the numbers of Arab American immigrant youth in schools is increasing, there is little understanding of their mental health and the sociocultural factors that might influence it. This study examined the relationship between 2 sociocultural factors (i.e., acculturative stress and religious practices) and internalizing symptoms in first- and second-generation Muslim Arab American adolescents. Adolescents (n = 88) ages 11 to 18 completed measures related to acculturative stress, religious practices, inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 75 publications
1
18
1
Order By: Relevance
“…Additionally, female participants may face intergenerational conflicts on social-related relationships, especially with the opposite gender and honor-related issues such as marriage and dating (Rasmi et al, 2014). Another study of Muslim Arab American adolescents found that younger participants with greater affiliation to the Arab culture had higher AS than older participants (Goforth et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, female participants may face intergenerational conflicts on social-related relationships, especially with the opposite gender and honor-related issues such as marriage and dating (Rasmi et al, 2014). Another study of Muslim Arab American adolescents found that younger participants with greater affiliation to the Arab culture had higher AS than older participants (Goforth et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the acculturative stressors may include social, attitudinal, familial, and environmental factors (Mena et al, 1987). Goforth et al (2016) noted that second-generation ArAm may face conflicts in balancing the differing value systems of their parents and peers; intergenerational conflicts or contradictory identities may contribute to undue stress. The findings from research on AS among ArAm have been inconsistent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…School psychologists are designated child advocates who are expected to provide culturally responsive practices (Goforth, Pham, Chun, Castro-Olivo, Yosai, 2016; National Association of School Psychologists, 2010). Indeed, school psychologists play a critical role in facilitating a supportive environment for Arab American students to acculturate healthily.…”
Section: Discussionmentioning
confidence: 99%
“…At the systems level, school psychologists can invite school staff to examine their biases, either as an open suggestion or through structured cultural competency trainings or meetings. In disseminating information about Arab culture and perhaps religious practices of some Arabs (Islam), it is important to be cautious that stereotypic information is not perpetuated (Goforth et al., 2016). School psychologists can work with school staff to review curriculum coverage of Arab history and culture, and provide formal opportunities within the school setting for students to express themselves culturally.…”
Section: Discussionmentioning
confidence: 99%